Inhibitive Action of Ferrous Gluconate on Aluminum Alloy in Saline Environment - Patricia Abimbola Idowu Popoola; Sanni Omotayo; Cleophas A. Loto; Olawale Muhammed Popoola (Advances in Materials Science and Engineering)
The corrosion of aluminum in saline environment in the presence of ferrous gluconate was studied using weight loss and linear polarization methods. The corrosion rates were studied in different concentrations of ferrous gluconate 0.5, 1.0, 1.5, and 2.0 g/mL at 28°C. Experimental results revealed that ferrous gluconate in saline environment reduced the corrosion rate of aluminum alloy at the different concentrations studied. The minimum inhibition efficiency was obtained at 1.5 g/mL concentration of inhibitor while the optimum inhibition efficiency was achieved with 1.0 g/mL inhibitor concentration. The results showed that adsorption of ferrous gluconate on the aluminium alloy surface fits Langmuir adsorption isotherm. The potentiodynamic polarization results showed that ferrous gluconate is a mixed type inhibitor. Ferrous gluconate acted as an effective inhibitor for aluminium alloy within the temperature and concentration range studied. The data obtained from weight loss and potentiodynamic polarization methods were in good agreement.